Hubungan Pengetahuan Ibu Dengan Pemberian Imunisasi HPV Di Puskesmas Pemurus Dalam - Wafa Wafa; Rusmilawaty Rusmilawaty; Rafidah Rafidah; Erni Yuliastuti (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2025)
Abstract Background: Cervical cancer is cancer that grows in the cervix, originating from the epithelium, or outer surface layer of the cervix, and 99.7% is caused by the HPV (Human Papilloma Virus) virus. The most commonly identified HPV viruses in cervical cancer are HPV types 16 and 18. Data from the Banjarmasin City Health Office states that of the 27 health centers spread throughout the city of Banjarmasin in 2023, Puskesmas Pemurus Dalam is ranked 18th with a target of 220 HPV immunization for 5th grade elementary school children who get immunized 181 people (82.3%) below the Banjarmasin City target of 95%. Objectives: Identifying the provision of HPV immunization, identifying maternal knowledge and analyzing the relationship between maternal knowledge and the provision of HPV immunization at Pemurus Dalam Health Center in 2024. Method: Using cross sectional method. The population is all mothers who have daughters in grade 5 SD in the Pemurus Dalam Health Center area with a total of 220 people with a quota sampling technique sample of 69 people. Analysis used with the Chi-Square test Results: Of the 69 respondents who did not get HPV immunization as many as 39 people (56.5%), and poor maternal knowledge as many as 29 people (42.1%) This study shows there is a relationship with the results of statistical tests obtained P-Value 0.003. Conclusion: There is a relationship between maternal knowledge and the provision of HPV immunization at Pemurus Dalam Health Center in 2024. Keywords: HPV Immunization, Maternal Knowledge